A polymorphism in the promoter of FRAS1 is a candidate SNP associated with metastatic prostate cancer. Issue 10 (6th May 2021) - Wang, Victoria; Geybels, Milan S.; Jordahl, Kristina M.; Gerke, Travis; Hamid, Anis; Penney, Kathryn L.; Markt, Sarah C.; Freedman, Matthew; Pomerantz, Mark; Lee, Gwo‐Shu M.; Rana, Huma; Börnigen, Daniela; et al.
Abstract: Background: Inflammation and one of its mediators, NF‐kappa B (NFκB), have been implicated in prostate cancer carcinogenesis. We assessed whether germline polymorphisms associated with NFκB are associated with the risk of developing lethal disease (metastases or death from prostate cancer). Methods: Using a Bayesian approach leveraging NFκB biology with integration of publicly available datasets we used a previously defined genome‐wide functional association network specific to NFκB and lethal prostate cancer. A dense‐module‐searching method identified modules enriched with significant genes from a genome‐wide association study (GWAS) study in a discovery data set, Physicians' Health Study and Health Professionals Follow‐up Study (PHS/HPFS). The top 48 candidate single nucleotide polymorphisms (SNPs) from the dense‐module‐searching method were then assessed in an independent prostate cancer cohort and the one SNP reproducibly associated with lethality was tested in a third cohort. Logistic regression models evaluated the association between each SNP and lethal prostate cancer. The candidate SNP was assessed for association with lethal prostate cancer in 6 of 28 studies in the prostate cancer association group to investigate cancer associated alterations in the genome (PRACTICAL) Consortium where there was some medical record review for death ascertainment which also had SNP data from the ONCOARRAY platform. All men self‐identified as Caucasian. Results: The rs1910301 SNP which was reproducibly associated with lethal disease was nominally associated with lethal disease (odds ratio [OR] = 1.40; p = .02) in the discovery cohort and the minor allele was also associated with lethal disease in two independent cohorts (OR = 1.35; p = .04 and OR = 1.35; p = .07). Fixed effects meta‐analysis of all three cohorts found an association: OR = 1.37 (95% confidence interval [CI]: 1.15–1.62, p = .0003). This SNP is in the promoter region of FRAS1, a gene involved in epidermal‐basement membrane adhesion and is present at a higher frequency in men with African ancestry. No association was found in the subset of studies from the PRACTICAL consortium studies which had a total of 106 deaths out total of 3263 patients and a median follow‐up of 4.4 years. Conclusions: Through its connection with the NFκB pathway, a candidate SNP with a higher frequency in men of African ancestry without cancer was found to be associated with lethal prostate cancer across three well‐annotated independent cohorts of Caucasian men.